The The Role of TPSq in Partisipatory Learning: Accumulation of Knowledge - fika palupi; Basori Basori; Cucuk Wawan Budiyanto (IJER (Indonesian Journal of Educational Research), 2020)
Efforts to improve the quality of education in Indonesia are carried out through improving infrastructure, competent educators, and improving the quality of graduates. However, the quality of education in some areas still needs attention. One of them is the amount of material content that is not proportional to the applied learning model. The use of expository learning models has become a habit for most teachers in Indonesia. Even though the implementation of the learning causes low learning outcomes and student participation. The application of participatory learning can be done through group activities and critical thinking. This study aims to determine the role of think pair square learning in participatory learning. This study uses a quantitative approach by determining the sample class through the cluster-sampling-area technique. The experimental class applies the think pair square cooperative learning model and the control class applies the expository learning model. Data retrieval is done through the method of learning outcomes tests, questionnaires and observations. The results showed an increase not only in student learning participation, but also in student learning outcomes. The involvement of students in learning activities caused through group activities led to high student participation in the experimental class by 26% compared to the control class by 2%. The application of participatory learning that is carried out effectively is able to increase student participation in learning activities. This is shown through students' self-confidence when interacting in one group to another.